Morphological, karyological features and pollen morphology of endemic Ebenus haussknechtii Bornm. ex Hub.-Mor. from Turkey: A traditional medicinal herb - Hayta, Sukru; Tasar, Neslihan; Cakilcioglu, Ugur; Gedik, Osman (Elsevier Gmbh, 2014)
In this study, morphological, morphometrical, karyological and detailed pollen morphology of Ebenus haussknechtii endemic to Turkey was studied for the first time. In the morphologic study, some morphological and morphometrical features of the plant were observed and compared with the published findings in the Flora of Turkey. Karyogram and idiograms of the plant were also prepared. The chromosome number of E. haussknechtii was determined as 2n = 14 and haploid karyotype formula 5 m + 1 sm + 1M. Metaphase chromosome length ranged from 2.16 to 1.93 mu m and the total haploid chromosome length was 17.90 mu m. The results of the light microscope investigation of the pollen revealed that the pollen grains were radially symmetrical, isopolar, tricolpate and prolate. Measurement of the reticulum heterobrachate indicated their ornamentation to be reticulate. (C) 2014 Elsevier GmbH. All rights reserved.
Keywords: Ebenus haussknechtii; Karyotype; Morphology; Polen; Medicinal plant; Turkish endemic